2021
DOI: 10.1016/j.jenvman.2020.111601
|View full text |Cite
|
Sign up to set email alerts
|

Trade-off analysis of cost and nutrient efficiency of coffee farms in vietnam: A more generalised approach

Abstract: Analysis of economic and environmental performance of agricultural production has received increasing attention in both the theoretical and empirical literature (Aldieri et al., 2019). Several methodological approaches have been proposed to measure environmental efficiency and to analyse trade-offs between economic and environmental performance (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Minimising chemical and water use will lead to more cost-effective coffee production in the longer term. Adopting SAPs is one way to move towards sustainable certified coffee farms which can perform better than their non-certified counterparts in both economic and environmental aspects (Ho et al, 2021). Coffee is mostly consumed in developed countries where consumers are willing to pay a higher price for organically and/or ethically produced coffee (Hainmueller et al, 2015).…”
Section: Coffee Production In Vietnammentioning
confidence: 99%
“…Minimising chemical and water use will lead to more cost-effective coffee production in the longer term. Adopting SAPs is one way to move towards sustainable certified coffee farms which can perform better than their non-certified counterparts in both economic and environmental aspects (Ho et al, 2021). Coffee is mostly consumed in developed countries where consumers are willing to pay a higher price for organically and/or ethically produced coffee (Hainmueller et al, 2015).…”
Section: Coffee Production In Vietnammentioning
confidence: 99%
“…In recent years, trade-off analysis has gradually become a research focus. Previous studies have explored four types of ESs (provisional, regulatory, cultural and supporting services) [12][13][14] and subtypes within specific types, such as freshwater and food supply [15]. Previous studies have shown that trade-off analysis is a key issue for planning, management, and decisionmaking within ESs [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The Vietnamese Ministry of Agriculture and Rural Development (MARD) addresses economic efficiency while concerned with sustainability and environmental conservation. Eventually, in recent years, the national and local governments have contributed to the success of perennial crop sectors by implementing various policies that are considered to improve farmers' technical, economic, and environmental efficiency (Ho et al, 2021).…”
Section: Introductionmentioning
confidence: 99%